Dredging—A conservative treatment for odontogenic tumor of jaws. Issue 5 (September 2017) - Acharya, Pradeep; Jaisani, Mehul Rajesh; Dongol, Ashok; Yadav, Ram Prasad; Bhattarai, Nilima; Mahat, Arun Kumar
Abstract: Odontogenic tumors of jaws are aggressive in nature with different clinical features and histological patterns. Management of the odontogenic tumors has been one of the most controversial entities because of its large, rapid growth, high recurrence rate with a need for resection of mandible which is associated with number of complications such as loss of jaw bone support, deformity, dysfunction and psychological distress. There are various treatment modalities from conservative to radical approach, but studies have shown that even alternative conservative approach like dredging can achieve good results. In this paper we discuss treatment of odontogenic tumors by dredging method with a report of our three cases.